Exploring Attitudes Towards Counterfeiting in the Luxury Product Industry (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this paper is to understand the consumer perception ofCounterfeit Luxury goods across ages and what consumer mentality triggers theconsumption of these goods and can be associated to the causality to their rise inpopularity